Supply Chain Performance Measurement Using Scor Model-Based Key Performance Indicators - Amelia Amelia (Jurnal Indonesia Sosial Teknologi, 2025)
This study presents a systematic approach to measuring supply chain performance using the Supply Chain Operations Reference (SCOR) model-based Key Performance Indicators (KPIs). Increasing global competition and post-pandemic supply chain disruptions have made performance measurement a critical priority for organizations seeking operational excellence. Despite the widespread adoption of the SCOR model, existing literature reveals significant gaps in its application within emerging economies and sector-specific contexts. This research employs a quantitative descriptive methodology, drawing on data from 120 respondents representing procurement, logistics, and operations functions across manufacturing firms. Using the five SCOR dimensions—Plan, Source, Make, Deliver, and Return—a total of 25 KPIs were assessed through structured surveys and validated through confirmatory factor analysis. Results indicate that the Deliver and Source dimensions record the lowest performance scores, signaling critical bottlenecks in distribution networks and supplier management. The study also reveals that organizations with integrated digital monitoring systems outperform traditional counterparts in three out of five SCOR dimensions. Findings contribute both theoretically, by extending the SCOR framework to manufacturing contexts in developing regions, and practically, by offering a diagnostic KPI dashboard for supply chain managers. This research underscores the urgency of evidence-based performance measurement as a foundation for supply chain resilience and sustainable competitive advantage.